Fluoro-substitution in hydrogen bonding liquid crystal benzoic acid: dielectric, electro-optic and optical proprieties and inducing polar nematic phase. Issue 5 (8th April 2020) - Fouzai, Malek; Guesmi, Ahlem; Hamadi, Naoufel Ben; Soltani, Taoufik
ABSTRACT: Dielectric and electro-optic properties have been studied in order to understand the effect of the fluoro-substitution on hydrogen bonded liquid crystal proprieties. The fluoro-substitution alters the characteristics of pure LC structure and changes its physical parameters. In the present paper, variation in physical parameters like dielectric permittivity, response time, elastic constant, rotational viscosity etc. has been explained based on many factors. In addition, the fluorine substitution has lead to the appearance of the polar nematic phase. Graphical Abstract: